2009
DOI: 10.1371/journal.pone.0007602
|View full text |Cite
|
Sign up to set email alerts
|

Male Perspectives on Incorporating Men into Antenatal HIV Counseling and Testing

Abstract: BackgroundMale partner involvement in antenatal voluntary HIV counseling and testing (VCT) has been shown to increase uptake of interventions to reduce the risk of HIV transmission in resource-limited settings. We aimed to identify methods for increasing male involvement in antenatal VCT and determine male correlates of accepting couple counseling in these settings.Methodology/Principal FindingsWe invited women presenting to a Nairobi antenatal clinic to return with their male partners for individual or couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
113
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(134 citation statements)
references
References 27 publications
17
113
3
1
Order By: Relevance
“…Studies across sub-Saharan Africa report rates of male partner HTC ranging from 5%-33%, with the majority reporting that less than one in five men get HIV tested during their partner's pregnancy (Figure 2). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] A retrospective evaluation of PMTCT medical records in a referral hospital in Uganda showed that less than 5% of male partners underwent HTC. 21 Another randomized trial in Uganda that offered a written invitation or information note resulted in only 15% male partner testing.…”
Section: Low Rates Of Male Partner Involvement In Pmtct and Antenatalmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies across sub-Saharan Africa report rates of male partner HTC ranging from 5%-33%, with the majority reporting that less than one in five men get HIV tested during their partner's pregnancy (Figure 2). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] A retrospective evaluation of PMTCT medical records in a referral hospital in Uganda showed that less than 5% of male partners underwent HTC. 21 Another randomized trial in Uganda that offered a written invitation or information note resulted in only 15% male partner testing.…”
Section: Low Rates Of Male Partner Involvement In Pmtct and Antenatalmentioning
confidence: 99%
“…21 Another randomized trial in Uganda that offered a written invitation or information note resulted in only 15% male partner testing. 11 In Kenya, uptake of male partner HTC was also approximately 15%, despite promotion of a male-friendly environment for individual or couple HIV testing, 5,13,14 and in a randomized clinical trial that offered couple versus individual HIV counseling and testing for couples in Tanzania, only 16% of men underwent couple HTC. 15 In Southern Africa, rates have been similar, with one study conducted among HIV-positive women in a district hospital in Malawi reporting male partner involvement of 14%.…”
Section: Low Rates Of Male Partner Involvement In Pmtct and Antenatalmentioning
confidence: 99%
“…Programs to prevent mother-to-child HIV transmission (PMTCT) have historically focused on women, to the exclusion of their male partners, resulting in low rates of HIV testing among men during their partners' pregnancies (Katz et al, 2009, Msuya et al, 2008, Chandisarewa et al, 2007. The underlying reasons likely include HIV-associated stigma (Greig et al, 2008, Montgomery et al, 2006, the perception that clinics are not "male-friendly" (Misiri et al, 2004, Falnes et al, 2011, Theuring et al, 2009, and the fact that men are not invited to participate (Mullany, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A screening rate of 83.3% and an HIV prevalence of 20% were observed among them. Some studies in Malawi, Tanzania and Kenya also report low male participation rates ranging from 3.5% to 16% [17][18][19].While male involvement in ANC and PMTCT of services resulted in increased uptake of antenatal care services in Nepal and United States of America [20][21][22], increase uptake and adherence to PMTCT interventions in Tanzania and Kenya [18,23] uptake of HIV testing by women in Tanzania and Uganda [24,25] an opportunity of male testing in Burkina Faso [26]. Recent systematic review has identified barriers to male involvement in PMTCT programs in sub-Saharan Africa [27,28].…”
Section: Discussionmentioning
confidence: 99%